Non-syndromic bilateral ovarian sex cord stromal tumor with annular tubules in a postmenopausal elderly woman as an incidental finding - Luna Limón, Claudia Gabriela; Ruíz Siller, Teresita de Jesús; Barboza Quintana, Oralia; Garza Guajardo, Raquel; Gómez Macías, Gabriela Sofía (2020)
tINTRODUCTION: Sex cord tumors with annular tubules (SCTAT) are very rare neoplasms comprising lessthan 1% of sex cord ovarian tumors. They usually occur in women of reproductive age and tend to beassociated with Peutz Jeghers Syndrome (PJS), be bilateral, multifocal, and small. When diagnosed inolder patients they are often described as sporadic, unilateral, predominantly cystic and bigger.CASE PRESENTATION: A bilateral hysterosalpingo-oophorectomy was performed in a seventy-one year-old-woman with postmenopausal bleeding showing no features of PJS. A bilateral SCTAT was diagnosed,associated with a focus of Leydig cell hyperplasia, an endometrial polyp and endomethroid intraepithelialneoplasia.DISCUSSION: SCTAT is a very rare histological variant in postmenopausal women. The case we present isspecial, different to what has been reported in the literature regarding these tumors.CONCLUSION: It is important to be aware that SCTATs can also be present in older women, they can bebilateral despite not being related to PJS syndrome and must be considered as a differential diagnosis inovarian tumors.